2013
DOI: 10.1159/000357171
|View full text |Cite
|
Sign up to set email alerts
|

The Limit of Anemia Tolerance during Hyperoxic Ventilation with Pure Oxygen in Anesthetized Domestic Pigs

Abstract: Background: During acellular replacement of an acute blood loss, hyperoxic ventilation (HV) increases the amount of O2 physically dissolved in the plasma and thereby improves O2 supply to the tissues. While this effect could be demonstrated for HV with inspiratory O2 fraction (FiO2) 0.6, it was unclear whether HV with pure oxygen (FiO2 1.0) would have an additional effect on the physiological limit of acute normovolemic anemia. Methods: Seven anesthetized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…28 They found that HV with FiO 2 100% only provided a marginal increase in anaemia tolerance compared with animals ventilated with FiO 2 60% in their previous study. 27,28…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…28 They found that HV with FiO 2 100% only provided a marginal increase in anaemia tolerance compared with animals ventilated with FiO 2 60% in their previous study. 27,28…”
Section: Discussionmentioning
confidence: 81%
“…27 Pape et al also examined whether HV with FiO 2 100% could increase anaemia tolerance and allow for a more extensive haemodilution compared to HV with FiO 2 60%. 28 They found that HV with FiO 2 100% only provided a marginal increase in anaemia tolerance compared with animals ventilated with FiO 2 60% in their previous study. 27,28 Much less information is available about the relationship between hyperoxaemia and tissue oxygenation during CPB.…”
Section: [ ]mentioning
confidence: 81%
See 1 more Smart Citation
“…As a consequence and without further treatment, animals die within 3 h after reaching the Hb(crit) [15]. By increasing the inspired O 2 concentration, an exaggerated level of hemodilution with a lower Hb(crit) can be reached [16]. …”
Section: Physiology Of Progressive Anemiamentioning
confidence: 99%
“…[13][14][15] Hb crit has been chosen as the primary endpoint in a variety of studies investigating the impact of interventions on the limit of tolerance to acute anemia. As reflected by reduced values of Hb crit (listed in table 2), tolerance to anemia was found to be increased by (1) hypothermia (moderate reduction of body core temperature reduces total body oxygen demand), 16 (2) hyperoxic ventilation (excellent bioavailability of oxygen physically dissolved in the plasma), 13,[17][18][19] (3) infusion of norepinephrine (stabilization of coronary perfusion pressure during hemodilution) 20 or infusion of artificial oxygen carriers (maintenance of arterial oxygen content despite reduced hematocrit), 15,21,22 (4) deep neuromuscular block (lowering skeletal muscular oxygen demand), 23 and (5) use of colloidal rather than crystalloid fluids for volume replacement (maintenance of microvascular perfusion due to reduced extravasation rate). 24 In contrast, tolerance to anemia was reduced by (1) hypovolemia (reduction of microcirculatory oxygen supply), (2) profound anesthesia (pharmacologic reduction of cardiac output), 25 and (3) coronary artery disease (reduced coronary flow reserve).…”
Section: Perioperative Medicinementioning
confidence: 99%